STRUCTURAL AND SEMANTIC FEATURES OF TERMS IN THE FIELD OF INTERNATIONAL TOURISM - Бушкова, Виктория; Сиборова, Оксана (SWorldJournal, 2020)
The paper covers some aspects of the study of the terms of international tourism on the material of the English language. The need for a more detailed study of the structural and semantic characteristics of tourism terms as well as peculiarities of their